Nuevos materiales bioinorgánicos de actividad antitumoral - Hernández Gorritti, Wilfredo Román (2014)
rhernand@ulima.edu.pe; beyinorg@chemic.uni-leipzig.de; jpascastillo@yahoo.es; espodine@ciq.uchile.cl; Abraham.vaisberg@upch.pe